The Effect of Cd and Nb on Bi-1212 System - Awang Teh, Azman (2004)
The 1212 phase of Bi-based superconductor by theory has good properties in terms of structure and transition temperature, as it is an adaptation of the Y123 system and the Bi22 12 system. The new Bi1212 system with stoichiometries (Bi0.2Pb0.6Mx)Sr2(Y0.3Ca0.7)Cu2.05O and ( B ~ ~ . ~ P ~ ~(, ~ ~~M. ,~) s~~a~ w ~he.re ~M =) C~d anud N~b, .x =~ 0, ~0.005, 0~.1, 0.15, 0.2,0.25 has been successfully synthesized and characterized by means of X-Ray (powder) diffraction, scanning electron microscope, AC susceptibility and resistivity measurements. For the composition of ( B ~ ~ , ~ P ~ ~ , ~ M ~ ) sth~e ~ ( Y ~ , above stated systematic examinations clarified the effect of Cd and Nb on Bi-1212 phase, both as a substitution (0 < x i 0.2) and as an addition (x = 0.25). All samples were prepared using solid-state reaction. These samples underwent sintering process at two different temperatures, which were 960°C and 980°C, for a time duration of 2 hours and 10 hours. Then all the samples underwent heat treatment in flowing argon at 750°C for 10 hours. All the samples were orthorhombic with the space group Pmmm except the compounds with composition ( ~ i ~ ~ ~ (~ ~b~~, ~~ ~ a~ ~dan,d ~~ ,) ~~ u~ ~) ( ~ i ~ ~ ~ (~ ~b~ ~, ~, ~~a ~~w.~hic~hd w)er~e suin~te~re~d. at~~ 96~0)°C0 f~o~r 2r, ho u~rs were tetragonal with space group P4mmm. The X-ray diffraction pattern showed that all samples were in mixed phase (12 12 and 221 2) with 12 12 acting as a dominant phase. All as-prepared samples showed non-superconducting properties below 20 K, but after heat treatment in flowing argon, some of them showed superconducting properties with the highest transition temperature of Tc,ze,,=64 K and Tc, ,,,et=80 K obtained from Nb-doping sample with x=0.2. The ac susceptibility studies showed that most of the superconducting material exhibited weak grain conductivity. The surface morphology of most of the samples observed from scanning electron microscope showed a layered-slab texture.